Mycorrhizal fungus BJ1, a new species of Tulasnella sp.: its biological characteristics and promoting effect on seed germination of Bletilla striata - Li, Zhengmei; Ye, Yueyu; Wang, Xia; Peng, Suyu; Chen, Beibei; Li, Shiqing; Chen, Haimin; Yang, Dongfeng; Jiang, Fusheng; Zhang, Chunchun; Li, Meiya (Frontiers in Plant Science, 2025)
Mycorrhizal fungi have been shown to promote seed germination and seedling growth in Orchidaceae plants. In the present study, a mycorrhizal fungus designated as BJ1 was isolated from the roots of Bletilla striata (Thunb.) Reiehb.f. Fluorescence staining and morphological analysis revealed that this fungus exhibited characteristics highly similar to those of Tulasnella. Subsequently, the strain was confirmed as a new strain of Tulasnella through sequencing and phylogenetic analysis of four loci: the internal transcribed spacer region ITS1-ITS4 (ITS), ATP synthase (C14436), glutamate synthase (C4102), and ATP deconjugase (C3304). Additionally, we investigated the in vitro biological activity of strain BJ1 and its effects on germination and growth of B. striata seeds. The results indicated that BJ1 is capable of producing plant cell-degrading enzymes, including pectinase and protease. Furthermore, it demonstrates an ability to solubilize inorganic phosphorus and synthesize indoleacetic acid (IAA). Nevertheless, it does not exhibit laccase activity or possess the capacity to produce siderophores, nor can it solubilize organic phosphorus. Microscopic observations revealed that strain BJ1 mainly colonizes the base of the B. striata protocorm, thereby enhancing seed germination, growth, and expansion. Notably, by the fourth week of germination, 74.23% of seeds in the symbiotic group had developed to stage 5, a significantly higher proportion compared to 50.43% in the non-symbiotic group. Additionally, the length, width, and fresh weight of seeds in the symbiotic group were 2.2 times, 1.8 times, and 3.7 times greater than those in the non-symbiotic group, respectively. Furthermore, by adding L-tryptophan as a substrate during co-cultivation with BJ1, there was a significant enhancement in IAA synthesis capability; this also led to a marked acceleration in the symbiotic germination process of B. striata seeds. These results suggest that strain BJ1 holds significant potential for application in the artificial propagation of B. striata seedlings. It can enhance propagation efficiency and improve seedling quality, thereby playing a crucial role in the conservation and sustainable development of germplasm resources of endangered orchids.